Complex Fourier Series Mathematical Model of a Three-Phase Inverter with Improved PWM Output Voltage Control - Zaskalicky, P.; Dobrucky, B. (Elektronika ir Elektrotechnika, 2012)
The presented article steady state analysis of a three-phase voltage source inverter with PWM output voltage control is proposed. The mathematical model is built on condition of assumption of idealized semiconductor devices. A complex Fourier series approach is used to predict the waveforms of the terminal output inverter voltages. On the basis of the developed voltage formula the load current waveform for the wye load connections are calculated. Ill. 9, bibl. 8 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.123.7.2376